2023
DOI: 10.1002/advs.202301606
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of the c‐Ring Promotes the Curvature Sorting of Monomeric ATP Synthases

David Valdivieso González,
Marcin Makowski,
M. Pilar Lillo
et al.

Abstract: ATP synthases are proteins that catalyse the formation of ATP through the rotatory movement of their membrane‐spanning subunit. In mitochondria, ATP synthases are found to arrange as dimers at the high‐curved edges of cristae. Here, a direct link is explored between the rotatory movement of ATP synthases and their preference for curved membranes. An active curvature sorting of ATP synthases in lipid nanotubes pulled from giant vesicles is found. Coarse‐grained simulations confirm the curvature‐seeking behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Similar curvature footprints were obtained in the different membrane compositions used, suggesting that fundamental aspects of protein–lipid interactions (i.e., hydrophobic mismatch) have a predominant role in determining the local curvature environment; however, minor differences arising from varying membrane compositions or enrichment of particular lipids around proteins could be functionally relevant. A number of studies have endeavored to determine the energetics of membrane deformation around curvature-inducing TM proteins. In general, it has been shown that it is less costly for the membrane to deform than for lipids to redistribute, and although both processes likely occur to varying degrees, the effect of membrane composition on extent of deformation is minor . It is important to note that while the simulations were carried out in a systematic manner, several different approaches were used to obtain the reference data.…”
Section: Resultsmentioning
confidence: 99%
“…Similar curvature footprints were obtained in the different membrane compositions used, suggesting that fundamental aspects of protein–lipid interactions (i.e., hydrophobic mismatch) have a predominant role in determining the local curvature environment; however, minor differences arising from varying membrane compositions or enrichment of particular lipids around proteins could be functionally relevant. A number of studies have endeavored to determine the energetics of membrane deformation around curvature-inducing TM proteins. In general, it has been shown that it is less costly for the membrane to deform than for lipids to redistribute, and although both processes likely occur to varying degrees, the effect of membrane composition on extent of deformation is minor . It is important to note that while the simulations were carried out in a systematic manner, several different approaches were used to obtain the reference data.…”
Section: Resultsmentioning
confidence: 99%